The global divide in data-driven farming - Mehrabi, Zia; McDowell, Mollie J.; Ricciardi, Vincent; Levers, Christian; Martínez, Juan Diego; Mehrabi, Natascha; Wittman, Hannah; Ramankutty, Navin; Jarvis, Andy (Springer, 2020)
Big data and mobile technology are widely claimed to be global disruptive forces in agriculture that benefit small-scale farm-ers. Yet the access of small-scale farmers to this technology is poorly understood. We show that only 24–37% of farms of <1 ha in size are served by third generation (3G) or 4G services, compared to 74–80% of farms of >200 ha in size. Furthermore, croplands with severe yield gaps, climate-stressed locations and food-insecure populations have poor service coverage. Across many countries in Africa, less than ~40% of farming households have Internet access, and the cost of data remains prohibitive. We recommend a digital inclusion agenda whereby governments, the development community and the private sector focus their efforts to improve access so that data-driven agriculture is available to all farmers globally.